Capobula gen. nov., a new Afrotropical dark sac spider genus related to Orthobula Simon, 1897 (Araneae: Trachelidae) - Haddad, Charles R.; Jin, Chi; Platnick, Norman I.; Booysen, Ruan (Zootaxa, 2021)
A new genus of the spider family Trachelidae L. Koch, 1872 from the Afrotropical Region is described. Capobula gen. nov. is represented by five species, known from South Africa and Lesotho only. Adults of both sexes of Orthobula infima Simon, 1896a, which is widely distributed in the Western Cape, South Africa, are described for the first time, and this species is transferred to Capobula gen. nov. as its type species. Four new species are described: C. capensis spec. nov. and C. neethlingi spec. nov. (South Africa: Western Cape), C. montana spec. nov. (Lesotho and South Africa: Eastern Cape, Free State and KwaZulu-Natal) and C. ukhahlamba spec. nov. (South Africa: KwaZulu-Natal). A phylogenetic analysis based on the cytochrome oxidase subunit I (COI) gene, including 14 genera of Trachelidae, one genus of Clubionidae Wagner, 1887 and three genera of Phrurolithidae Banks, 1892, supports the placement of Capobula gen. nov. in Trachelidae, with Orthobula Simon, 1897 as its likely closest relative.